(untitled) (Conferencea, 2024)
This thesis focuses on the issue of the phenomenon of polsiemia in Uzbek and its study in terms of linguistics. Also, reflecting on his initial views on the police incident, Uzbek linguists analyzed their scientific views on the incident. Language is always mobile, a system that continues to develop. The phenomenon of poliemia plays a prominent role in any language. Language wealth is measured not only by words, phrases, but also by the linguistic meanings of words. Therefore, the abundance of words is that polynemia has its place in the vocabulary of the language.